The language of literacy education - Collet, Vicki (Boston ; Leiden : Brill, 2021)
"This volume is a valuable reference for literacy scholars and educators. In this encyclopaedic reference of prominent literacy terms, you will find citations of theorists and research findings to validate the content and lead you into a deeper dive for those terms of particular interest. Whether read cover to cover to provide an overview of the field or used as a side-table reference, The Language of Literacy Education offers valid, current information about important topics in the field. The 297 indexed terms expand our 87 main entries to encompass relevant terms in literacy education. Contributors are: Johnny B. Allred, Leah R. Cheek, Vicki Stewart Collet, Rebecca Carpenter de Cortina, Judy L. Fields, Seth D. French, Savanna L. Gragg, Angelia C. Greiner, Megan Yates Grizzle, Kathryn Hackett-Hill, Holly Sheppard Riesco, Afton Schleiff and Wyann Stanton"--
Preface and Introduction -- Notes on Contributors -- Annotation -- Argumentative Writing -- Assessment -- Background Knowledge -- Biliteracy -- Close Reading -- Comprehension -- Comprehension Strategies -- Comprehensive Literacy Instruction -- Construction-Integration (CI) Model -- Context -- Contextual Reading Model -- Critical Literacy and Critical Media Literacy -- Cueing Systems -- Culturally Responsive Instruction -- Decoding -- Differentiation -- Digital Literacies -- Direct Instruction -- Disciplinary Literacy -- Discourse Analysis -- Discussion -- Dyslexia -- Embodied Literacies -- Emergent Literacy -- Fluency -- Four-Part Mental Processor -- Genre -- Gradual Release of Responsibility -- Grammar and Mechanics -- Graphic Organizers -- Guided Reading/Writing -- Independent Reading/Writing -- Informational text Integrated Instruction -- Intervention -- Language Development -- Learning Progressions -- Literacy/Literacies -- Literary Devices -- Mentor Texts -- Miscue Analysis -- Modeling -- Morphology -- Motivation -- Multicultural Literature -- Multimodality -- Narrative Text -- New Literacies -- Peer Response -- Perspective and Point of View -- Phonics -- Phonological and Phonemic Awareness -- Pragmatic Knowledge -- Question Answer Relationship -- Read Aloud -- Readability -- Reading Recovery -- Reading-Writing Relationships -- Reciprocal Teaching -- Rhetorical Factors and Devices -- Running Record -- Scafffolding -- Science of Reading -- Semantics -- Sentence Frames -- Shared Reading/Writing -- Sight Words -- Simple View of Reading -- Small-Group Instruction -- Sociocultural Perspective -- Standards -- Story Elements/Story Grammar -- Text Structures and Text Features -- Theme -- Thesis -- Think Aloud -- Transactional Theory -- Translanguaging -- Understanding -- Vocabulary Instruction -- Voice -- Workshop (Reading & Writing) -- Writing Process -- Zone of Proximal Development -- Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Literacy -- Terms and phrases; Literacy -- Study and teaching; Literacy; Literacy -- Study and teaching; Dictionaries